1996
DOI: 10.1093/ije/25.5.1083
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Risk Factors for Seropositivity to Human T-Lymphotropic Virus Type I (HTLV-I) in Jamaica

Abstract: These data confirm that heterosexual intercourse is a major route of HTLV-I transmission, but do not support suggestions of insect or environmental vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…14 The cases and asymptomatic carriers were unrelated and had similar age and geographic distributions.…”
Section: Study Subjectsmentioning
confidence: 97%
“…14 The cases and asymptomatic carriers were unrelated and had similar age and geographic distributions.…”
Section: Study Subjectsmentioning
confidence: 97%
“…Similarly to other sexually transmitted infections, sexual transmission of HTLV-1 is associated with unprotected sex, multiple sexual partners, lifetime contact with an HTLV-1-infected partner, the presence of genital sores or ulcers, and paying or receiving money for sex (65).…”
Section: Transmissionmentioning
confidence: 99%
“…In the past, this occurred mainly through the transfusion of blood not tested for HTLV-1. Most epidemiological studies of HTLV-1 reported transfusion as an important risk factor for HTLV-1 seropositivity (65). The highest risk is associated with the transfusion of packed red cells (92).…”
Section: Transmissionmentioning
confidence: 99%
“…Male-to-female transmission of HTLV-1 appears to be substantially more efficient (with a frequency of 60.8%) than the opposite route (with a frequency of 0.4%) (25), indicating that women are particularly at risk (25,34,35). This finding highlights the importance of developing strategies to prevent or reduce the sexual transmission of HTLV-1 and enable women to protect themselves by methods independent of, or in addition to, condom use.…”
Section: Discussionmentioning
confidence: 87%